Correction to: A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)

A stakeholder-guided marine heatwave hazard index for fisheries and aquaculture - Jules B. Kajtar; Neil J. Holbrook; Anna Lyth; Alistair J. Hobday; Craig N. Mundy; Sarah C. Ugalde (Climatic Change, 2024)
Marine heatwaves pose an increasing threat to fisheries and aquaculture around the world under climate change. However, the threat has not been estimated for the coming decades in a form that meets the needs of these industries. Tasmanian fisheries and aquaculture in southeast Australia have been severely impacted by marine heatwaves in recent years, especially the oyster, abalone, and salmon industries. In a series of semi-structured interviews with key Tasmanian fishery and aquaculture stakeholders, information was gathered about the following: (i) the impacts they have experienced to date from marine heatwaves, (ii) their planning for future marine heatwaves, and (iii) the information that would be most useful to aid planning. Using CMIP6 historical and future simulations of sea surface temperatures around Tasmania, we developed a marine heatwave hazard index guided by these stakeholder conversations. The region experienced a severe marine heatwave during the austral summer of 2015/16, which has been used here as a reference point to define the index. Our marine heatwave hazard index shows that conditions like those experienced in 2015/16 are projected to occur approximately 1-in-5 years by the 2050s under a low emissions scenario (SSP1-2.6) or 1-in-2 years under a high emissions scenario (SSP5-8.5). Increased frequency of marine heatwaves will likely reduce productivity by both direct (mortality) and in-direct (ecosystem change, greater incidence of disease) impacts on target species. The illustrative hazard index is one step towards a marine heatwave risk index, which would also need to consider aspects of exposure and vulnerability to be of greater utility to stakeholders.

Forecasting a Summer of Extremes: Building Stakeholder Response Capacity to Marine Heatwaves - Alistair Hobday; Claire Spillman; Jamie Allnutt; Melinda Coleman; Fred Bailleul; Laura Blamey; Stephanie Brodie; Arani Chandrapavan; Jason Hartog; David Maynard; Craig Mundy; Eva Plaganyi; et al. (Oceanography, 2024)
Forecasts of an El Niño in 2023/2024 raised concern among Australian marine stakeholders regarding its potential impacts on marine industries and systems. National level seafood-focused climate briefings were requested by the fisheries sector for the first time, driven by various state and regional level meetings and information requests. To respond to stakeholder needs, six virtual national marine climate briefings were undertaken through the austral 2023/2024 summer, underpinned by new subseasonal to seasonal marine heatwave forecast capabilities. These briefings were developed in collaboration with multiple science organizations and were targeted to industry and management authorities across the Australian seafood sector. As a result, targeted information products, additional regional and sector-specific briefings, and state response plans were developed. Collectively, these briefings were a catalyst for positive and rapid action in policy, management, industry, and research arenas. This experience showed that the combination of seasonal forecasting capability, inter-agency coordination, strong stakeholder engagement, and effective science communication plays a critical role in improving the understanding of, planning for, and responses to extreme events.